To change the bank account of BUCG-ABC Joint venture for revenue collection - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding the change of bank account of BUCG-ABC Joint venture for revenue collection for BRAC University new campus project.